2012
DOI: 10.15407/spqeo15.03.232
|View full text |Cite
|
Sign up to set email alerts
|

SERS of Rhodamine 6G on substrates with laterally ordered and random gold nanoislands

Abstract: Abstract. Preparation and study of laterally ordered and disordered arrays of Au nanoislands as SERS substrates are reported. Developed technology allows obtaining SERS substrates with long-term stability (up to six months), efficient (up to 10 4 ) and laterally homogenous enhancement of the Raman signal from molecular analyte. The substrates developed are suitable for Raman bio-diagnostics, because their plasmon resonance can be tuned within the range 700-900 nm that falls into the transparency window of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…47 Researchers used chemical and thermal evaporation methods to prepare noble metal nanoparticles on large scale substrate. 31,35,[48][49][50][51] The morphology of the SERS substrate in this work shows similarities to that in other work, with densely distributed noble metal nanoparticles. The advantage of the preparation method in this work is that a single layer of dense Au nanoparticles is distributed on the curved surface and gap region of SiO 2 microspheres, with nanoparticle spacing as small as 10 nm.…”
Section: Resultssupporting
confidence: 80%
“…47 Researchers used chemical and thermal evaporation methods to prepare noble metal nanoparticles on large scale substrate. 31,35,[48][49][50][51] The morphology of the SERS substrate in this work shows similarities to that in other work, with densely distributed noble metal nanoparticles. The advantage of the preparation method in this work is that a single layer of dense Au nanoparticles is distributed on the curved surface and gap region of SiO 2 microspheres, with nanoparticle spacing as small as 10 nm.…”
Section: Resultssupporting
confidence: 80%
“…Most clear effect of annealing manifested in the gold plasmonic structures. In [ 18 ] samples of thermally deposited gold layers with an effective thickness from 1 to 12 nm were investigated in detail, in particular, the effect of annealing in air at temperatures from 250 to 450 °C on morphological and optical properties of disordered Au nanoislands. It was found that in the temperature range 350–450 °C, Au nanoislands of the spherical and ellipsoidal shapes are formed, and the morphology of the Au island film and their plasmon resonance spectrum depends noticeably on the nominal Au thickness and post-annealing temperature, while the duration of annealing is of minor importance.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, many various types of SERS substrates are known. The most widespread of them are based on laterally ordered [18] or disordered [19,20] arrays of silver or gold nanoparticles deposited onto dielectric wafers. However, their fabrication, as a rule, requires a high-tech equipment and is rather expensive.…”
Section: Introductionmentioning
confidence: 99%